1996
DOI: 10.1055/s-2007-1015730
|View full text |Cite
|
Sign up to set email alerts
|

Der Wert der MR-Mammographie in der Differentialdiagnostik von non-puerperaler Mastitis und inflammatorischem Mammakarzinom bei 1,5 Tesla

Abstract: MRM proved useful in the follow-up of treated mastitis to demonstrate the success of antibiotic treatment of mastitis and to diagnose a histologically unconfirmed inflammatory carcinoma by means of a different follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Moreover, in several studies, mammary ductal ectasia has been found to be responsible for 5–25% of all symptomatic breast conditions [ 4 , 5 ]. The clinical presentations of PDM are not specific and are easily confused with breast carcinoma in imaging manifestations [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in several studies, mammary ductal ectasia has been found to be responsible for 5–25% of all symptomatic breast conditions [ 4 , 5 ]. The clinical presentations of PDM are not specific and are easily confused with breast carcinoma in imaging manifestations [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Auch bei Vorliegen inflammatorischer Mammaveränderungen ± insbesondere zur Differenzierung zwischen einer Mastitis und einem inflammatorischen Mammacarcinom ± ist die MRM wenig hilfreich [34]. Auch bei Vorliegen inflammatorischer Mammaveränderungen ± insbesondere zur Differenzierung zwischen einer Mastitis und einem inflammatorischen Mammacarcinom ± ist die MRM wenig hilfreich [34].…”
Section: Indikationen Für Die Mrmunclassified